A two-dose viral-vectored Plasmodium vivax multistage vaccine confers durable protection and transmission-blockade in a pre-clinical study - Yamamoto, Yutaro; Fabbri, Camila; Okuhara, Daiki; Takagi, Rina; Kawabata, Yuna; Katayama, Takuto; Iyori, Mitsuhiro; Hasyim, Ammar A.; Sakamoto, Akihiko; Mizukami, Hiroaki; Shida, Hisatoshi; Lopes, Stefanie; et al. (Frontiers in Immunology, 2024)
Among Plasmodium spp. responsible for human malaria, Plasmodium vivax ranks as the second most prevalent and has the widest geographical range; however, vaccine development has lagged behind that of Plasmodium falciparum, the deadliest Plasmodium species. Recently, we developed a multistage vaccine for P. falciparum based on a heterologous prime-boost immunization regimen utilizing the attenuated vaccinia virus strain LC16m8Δ (m8Δ)-prime and adeno-associated virus type 1 (AAV1)-boost, and demonstrated 100% protection and more than 95% transmission-blocking (TB) activity in the mouse model. In this study, we report the feasibility and versatility of this vaccine platform as a P. vivax multistage vaccine, which can provide 100% sterile protection against sporozoite challenge and >95% TB efficacy in the mouse model. Our vaccine comprises m8Δ and AAV1 viral vectors, both harboring the gene encoding two P. vivax circumsporozoite (PvCSP) protein alleles (VK210; PvCSP-Sal and VK247; -PNG) and P25 (Pvs25) expressed as a Pvs25–PvCSP fusion protein. For protective efficacy, the heterologous m8Δ-prime/AAV1-boost immunization regimen showed 100% (short-term; Day 28) and 60% (long-term; Day 242) protection against PvCSP VK210 transgenic Plasmodium berghei sporozoites. For TB efficacy, mouse sera immunized with the vaccine formulation showed >75% TB activity and >95% transmission reduction activity by a direct membrane feeding assay using P. vivax isolates in blood from an infected patient from the Brazilian Amazon region. These findings provide proof-of-concept that the m8Δ/AAV1 vaccine platform is sufficiently versatile for P. vivax vaccine development. Future studies are needed to evaluate the safety, immunogenicity, vaccine efficacy, and synergistic effects on protection and transmission blockade in a non-human primate model for Phase I trials.